Active PKG II inhibited the growth and migration of ovarian cancer cells through blocking Raf/MEK and PI3K/Akt signaling pathways. Issue 8 (13th August 2019) - Wu, Yan; Cai, Qin; Li, Wei; Cai, Zhensheng; Liu, Ying; Li, Hongfan; Pang, Ji; Chen, Yongchang
Abstract: Despite advances in chemotherapy, ovarian cancer (OC) is still the most lethal gynecologic malignancy. So, it is imperative to explore its mechanism and find novel targets to improve the outcome. Type II cyclic guanosine 3′, 5′-monophosphate (cGMP)-dependent protein kinase (PKG II) has been recently reported to inhibit proliferation and metastasis in several tumors. The present study is to clarify the effect of PKG II combined with l -arginine (l -Arg) on OC cells. SKOV3 and A2780 cells were infected with adenovirus coding cDNA of PKG II to increase PKG II expression and l -Arg was applied to activate this kinase. CCK8 assay, Transwell migration and TUNEL assay were applied to detect the proliferation, migration and apoptosis of the OC cells, respectively. Western blotting was used to detect the level of total and phosphorylated proteins. Our results showed that co-treatment with PKG II and l -Arg inhibited EGF-induced proliferation and the expression of Proliferating Cell Nuclear Antigen (PCNA), Cyclin E and N-Cadherin, whereas up-regulated the expression of E-Cadherin, abolished the anti-apoptotic effect of EGF, prevented the process of epithelial-to-mesenchymal transition (EMT) as well as blocked EGF-triggered Raf-MEK and phosphatidylinositol 3-kinase (PI3K)/Akt signaling pathways. Our results suggested that PKG II activated by l -Arg could inhibit proliferation and migration and promote the apoptosis of OC cells. Based on the above results and our previous data, it is speculated that PKG II is an inhibitor of cancer with extensive effects.